1998
DOI: 10.1002/(sici)1097-0215(19981023)79:5<468::aid-ijc4>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein expression and drug resistance in breast cancer patients treated with induction chemotherapy

Abstract: Heat shock proteins (Hsps) are induced in vitro by several cytotoxic drugs; in human breast cancer cells these proteins appear to be involved in anti-cancer drug resistance. The present report was designed to analyze whether chemotherapy affects in vivo the expression of Hsp27, Hsp70, Hsc70 and Hsp90 in breast cancer patients treated with induction chemotherapy and whether these proteins may be determinants of tumor resistance to drug administration. We have analyzed 35 biopsies from breast cancer patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
1
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 0 publications
4
92
1
8
Order By: Relevance
“…The overexpression of HSP27 or its murine analogue, HSP25, has been shown to protect mammalian cells exposed to a variety of stress stimuli, including heat shock, oxidative stresses, and chemotherapeutic agents (Richards et al 1996;Fortin et al 2000) probably by inhibiting the mitochondrial pathway of apoptosis (Mairesse et al 1998;Bruey et al 2000). Furthermore, several studies have demonstrated that the expression of HSP27 is increased in various human cancers, suggesting that the cytoprotective activity of HSP27 might aVect tumorigenesis and the susceptibility of tumors to cancer treatment (Richards et al 1996;Vargas-Roig et al 1998;Fortin et al 2000). Supporting this postulation, HSP27 expression was reported to be correlated with a poor prognosis after surgery or a resistance to adjuvant therapy in many types of cancers including gastric cancer, breast cancer, osteosarcoma, and prostate carcinoma (Paulus et al 1993;Nakopoulou et al 1995;Liu et al 1996;Uozaki et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of HSP27 or its murine analogue, HSP25, has been shown to protect mammalian cells exposed to a variety of stress stimuli, including heat shock, oxidative stresses, and chemotherapeutic agents (Richards et al 1996;Fortin et al 2000) probably by inhibiting the mitochondrial pathway of apoptosis (Mairesse et al 1998;Bruey et al 2000). Furthermore, several studies have demonstrated that the expression of HSP27 is increased in various human cancers, suggesting that the cytoprotective activity of HSP27 might aVect tumorigenesis and the susceptibility of tumors to cancer treatment (Richards et al 1996;Vargas-Roig et al 1998;Fortin et al 2000). Supporting this postulation, HSP27 expression was reported to be correlated with a poor prognosis after surgery or a resistance to adjuvant therapy in many types of cancers including gastric cancer, breast cancer, osteosarcoma, and prostate carcinoma (Paulus et al 1993;Nakopoulou et al 1995;Liu et al 1996;Uozaki et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, induction of HSPs by DDP has been documented in mammalian cells using a variety of approaches. Hsp90 induction by DDP or other antitumor drugs has been associated with drug resistance [77,78]. Finally, in this study, activation of recombinational repair after DDP damage was expected as S. pombe spends the majority of its time in the G2 phase, where repair of DNA lesions mainly occurs through recombination.…”
Section: Discussionmentioning
confidence: 57%
“…To date, the most widely studied cellular mechanisms of tumor resistance are still those associated with drug eZux mechanisms involving members transporter family, notably P-glycoprotein (P-gp), multidrug-resistant protein 1 (MRP1), and breast cancer resistance protein (BCRP) (Leonard et al 2003;Borst et al 2000). Furthermore, Many membrane transporters independent mechanisms also have been observed to be associated with MDR, such as Dickkopf-3 in MCF-7/ADR (Kawasaki et al 2009), caspase-6, -7, -8, -9 and -10 in MCF-7/doxorubicin (Park et al 2004) and Heat shock proteins (Hsps) associated with chemotherapy response in vivo (Vargas-Roig et al 1998).…”
Section: Introductionmentioning
confidence: 99%